Relapse analysis of irradiated patients within the HD15 trial of the German Hodgkin Study Group - Kriz, Jan; Reinartz, Gabriele; Dietlein, Markus; Kobe, Carsten; Kuhnert, Georg; Haverkamp, Heinz; Haverkamp, Uwe; Engenhart-Cabillic, Rita; Herfarth, Klaus; Lukas, Peter; Schmidberger, Heinz; Staar, Susanne; et al. (International journal of radiation oncology, biology, physics, 2015)
To determine, in the setting of advanced-stage of Hodgkin lymphoma (HL), whether relapses occur in the irradiated planning target volume and whether the definition of local radiation therapy (RT) used by the German Hodgkin Study Group (GHSG) is adequate, because there is no harmonization of field and volume definitions among the large cooperative groups in the treatment of advanced-stage HL.
Gesehen am 29.05.2020